Perancangan Sistem Informasi Data Alumni Berbasis Web Pada Prodi Manajemen Informatika Universitas Labuhanbatu - Siregar, Siti Wahdina; Harahap, Syaiful Zuhri; Irmayani, Deci (Journal of Computer Science and Information System(JCoInS), 2021)
Along with its development, the internet has a very important role in helping human performance, one of which is in helping educational institutions, especially universities, as a means of information. The internet, one of the media that can be used to accommodate all information about universities, is a website. With the development of information technology, especially the internet, which can help make work easier as the right medium to unite the alumni of the Labuhanbatu University Informatics Management Study Program.Alumni data have a very important role in the Labuhanbatu University Information Management Study Program, especially in reflecting quality in a tertiary institution in the public sphere. From year to year the number of alumni in the Labuhanbatu University Information Management Study Program is increasing, automatically more alumni data and the higher the number of needs to attract alumni in a forum. Almuniac data is one of the information systems designed to facilitate the work of managing data to provide complete data through web-based information services.